Strategi Pengembangan Kepribadian Positif Guru dalam Dunia Pendidikan Modern - Mursidin; Lulu Khoerunnisa; M. Akhsanul Kholiqin; Zahra Aprillyana Indah (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to identify the positive personality traits that teachers need to have, strategies for developing them, supporting and inhibiting factors, and their impact on the quality of learning. Using a descriptive qualitative method, data were obtained through interviews, observations, and documentation studies with Miles and Huberman's model analysis. The results show that integrity, empathy, adaptability, emotional intelligence, and enthusiasm for learning are important characteristics of modern teachers. Development strategies include professional training, supervision, a positive school culture, self-reflection, and coaching technology. Effectiveness is influenced by teacher motivation, leadership, and school support, but is hampered by workload and limited technological literacy. The implementation of these strategies has been proven to improve the quality of learning, teacher-student interaction, teacher professionalism, and create a more humanistic, collaborative, and sustainable growth-oriented educational environment.